The image of a psychologist and teacher in modern education. - Karimova M. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The influence of the image of a modern pedagogue in the educational process. The interpretation of the meaning of the image, the positive and negative effects of the image on the student are revealed. By its essence, pedagogical skill is a whole system. Pedagogical skill is revealed directly in professional-pedagogical activity.